Bentuk Mediatisasi hadis berupa Video: Respon Netizen Terhadap Video Pendek Mengenai Hadis di Aplikasi Tiktok - Shari, Mira Fitri (UIN Sunan Kalijaga Yogyakarta, 2021)
This paper discusses the form of mediatization of hadith in the form of short videos on tik-tok. By departing from the questions, a) what is the meaning of mediatization of hadith?, b) What are the forms of short videos about hadith on the Tiktok application?, c) how are netizens responding to these videos?. And by using a qualitative research method of documentation. Where, qualitative research is a process of research and understanding based on a methodology that investigates a social phenomenon and human problems. Documentation data is a data collection technique that involves document data sources in the form of written sources, images (photos), films, or monumental works and others, all of which can provide information for the research process. And in this research, what is being investigated is a short tiktok video containing the prophet’s hadiths. From this research, it was found that the types of videos in the tik-tok application vary. There is a hadith that was written and then added to the background of a beautiful scenery accompanied by Islamic songs or music. Then there is a hadith that was obtained from Twitter and then screenshot and added with a beautiful background accompanied by music or songs as well. Then there is also a video clip in the form of an explanation of the hadith taken from YouTube and there is also a video in the form of an explanation of the hadith by those who have an account and a background is added to the writings of the prophet’s hadith being explained. The explanations of hadith on social media are still textual and not contextual. Netizens’ responses to posts varied, but most of them felt helped in understanding religious teachings. But also not infrequently criticize the posts. And some then asked further asking for an explanation.